Pengaruh Keamanan Data, Tingkat Bunga, Biaya Admnistrasi Dan Kecepatan Persetujuan Terhadap Minat Penggunaan Pinjaman Online (Studi Kasus Pada Mahasiswa Prodi Manajemen Universitas Muhammadiyah Metro) - Imantoro, Jati; Widodo, Deny Edy; Wijanarko, Tiya Audi Erindha (Jurnal Manajemen DIVERSIFIKASI, 2023)
Improving the consumptive behavior of the community including students with the proliferation of market place applications, one of which is currently in great demand by students is the Shopee marketplace. This behavior is also followed by the ease with which people shop now by paying for their goods using the pay latter facility. The purpose of this study was to determine the effect of data security, interest rates, administrative costs and speed of approval on the interest in using online loans for students of the Muhammadiyah Metro University Management Study Program. The research design is quantitative research or verification research. The methods used in this study are data security, interest rates, administrative fees, speed of approval and interest in using online loans. The population and sample of the study were students of the Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro Batch 2018 with the number of samples taken as many as 68 students. Data collection techniques using questionnaires. The analytical tool used is data quality analysis and multiple linear regression analysis with SPSS program. The results showed that data security, interest rates, administrative fees, speed of approval partially or simultaneously influenced the interest in using online loans for Shopeepaylater.